Stem cell therapy for neurodegenerative disorders - Chaturvedi V.K.; Hangloo A.; Pathak R.K.; Gupta K.K.; Singh V.; Singh A.K.; Verma V.; Singh M.P. (My University, 2025)
Stem Cell technology has emerged as an attractive option to inspect and treat the neurodegenerative diseases. Stem cells defined as the cells having the capability to differentiate and the ability to self-renew. Since their discovery research in this area has continued to increase. However, studies indicated that the process of neurogenesis doestake place in the brain. Stem cell transplantation in animal models can improve the function of the cells by replacing the lost neurons and glial cells by arbitrate remyelination, trophic actions and modulation of inflammation. Neurodegenerative diseases are bug of the nervous system and their causes and treatments are enigmatic. So we could understand the mechanisms of action of stem cells after transplantation as well as to learn to control survival, migration, proliferation and differentiation of stem cells in the pathological environment. © 2017 by Nova Science Publishers, Inc. All rights reserved.